O uso empírico de antibióticos e a sepse severa induzida por Enterobacter spp. em neonato - Spironello, Ricardo Alexandre (2016)
This is a report on a case of neonatal sepsis and clinical management with multiple antibiotic therapy in a neonatal intensive care unit (NICU) in Brazil. A preterm baby boy was born by caesarean delivery at 34 weeks and two days of gestation from an oligodramnious pregnancy with intrauterine growth restriction. After respiratory failure detection, the baby was intubated and placed on mechanical ventilation for respiratory failure and was shifted to NICU. Ampicillin and gentamicin were instituted empirically. Enterobacter spp.-induced severe sepsis was diagnosed. Included in the antibiotic therapy were oxaciclin, amikacin, cefepime, tazocin, meropen and teicoplanin. After sixty days in NICU, clinical and laboratory parameters were normalized and the baby recovered. The empiric long-term antibiotic treatment and the use of broad spectrum antibiotics, as observed in the present case, should be carefully evaluated in newborns admitted to the NICU.